Role of baseline antral follicle count and anti-Mullerian hormone in the index stimulation cycle of IVF treatment in predicting outcome of subsequent frozen-thawed embryo transfers. (July 2014) - Li, H. W. Raymond; Lee, Vivian C. Y.; Lau, Estella Y. L.; Yeung, William S. B.; Ho, Pak-Chung; Ng, Ernest H. Y.
Abstract This retrospective cohort study aims at determining whether baseline antral follicle count (AFC) and serum anti-Mullerian hormone (AMH) level in the index stimulation cycle predict live-birth outcome in subsequent frozen-thawed embryo transfer (FET) cycles. We studied 500 women undergoing the first IVF cycle who had embryo(s) cryopreserved. The main outcome measures were live-birth in the first FET cycle and cumulative live-birth in all the FETs combined after the same stimulation cycle. Our results showed that baseline AFC and AMH level on the day before ovarian stimulation showed significant correlation. In the first FET cycle, AFC and AMH level were significantly higher in subjects attaining live-birth in the first FET cycle or cumulative live-birth from all FETs than those who did not. Both AMH and AFC were insignificant predictors of live-birth in the first FET cycle or cumulative live-birth after adjusting for age. The areas under the ROC curves for AMH, AFC and age were 0.654, 0.625 and 0.628, respectively, for predicting cumulative live-birth. In conclusion, we reported for the first time that baseline AFC and AMH in the index stimulation cycle have only modest predictive performance on cumulative live-birth in subsequent FET cycles.